2023
DOI: 10.1186/s12912-023-01276-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception of coronavirus disease (COVID-19) and its relationship with coping strategies and perceived social support in iranian people: a descriptive correlational study

Abstract: Background Perception of the threatening disease leads to coping behaviors that can affect the treatment process. Social support can be one of the factors influencing the perception of the disease and coping strategies. Our study aimed to determine the perception of the disease, its relationship with coping strategies and social support in COVID-19 patients in Iran. Methods This cross-sectional study was conducted on 1014 patients who were hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The review of the literature has revealed that most of the studies have considered the medical aspect of this pandemic such as background, prevention, symptoms, risks, complications, treatment, and the psychological and psychiatric effects of the disease [ 14 16 ]. Other studies in this field explored disease patterns based on social factors in an infected area [ 16 ], effects of bioenvironmental, social, and political approaches on the performance of some centers during the COVID-19 pandemic [ 17 ], and understanding of the disease and some social factors such as perceived social support [ 18 ]. To the best knowledge of the authors, there is not any study considered the social determinants of health comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the literature has revealed that most of the studies have considered the medical aspect of this pandemic such as background, prevention, symptoms, risks, complications, treatment, and the psychological and psychiatric effects of the disease [ 14 16 ]. Other studies in this field explored disease patterns based on social factors in an infected area [ 16 ], effects of bioenvironmental, social, and political approaches on the performance of some centers during the COVID-19 pandemic [ 17 ], and understanding of the disease and some social factors such as perceived social support [ 18 ]. To the best knowledge of the authors, there is not any study considered the social determinants of health comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Emotions play an important role, mainly anxiety, which affects functioning from the moment of exposure, through the onset of symptoms, the course of the disease, all the way to the rehabilitation period. All of these conditions affect the level of resilience to stress in a threatening situation and alter the repertoire of individual coping strategies as stereotypical behaviors [9].…”
Section: Introductionmentioning
confidence: 99%